A hypothetical model: Chromatin remodelers couple with acetyltransferases to trigger the elongation of RNA polymerase II (pol II) - Zhang, Gongyi (Frontiers in Epigenetics and Epigenomics, 2024)
Transcription is one of the central dogmas of life. Most genes in eukaryotes are transcribed by RNA polymerase II (Pol II). For Pol II to transcribe along the gene body, it must overcome nucleosomes, which are barriers for Pol II. It is still a mystery how Pol II ejects nucleosomes during transcription elongation. I hypothesize that a group of chromatin remodelers (SWI/SNF, RSC, SWR1, INO80) carry a group of histone acetyltransferases (NuA4, SAGA, NuA3) to deposit acetyl-groups on histone tails to generate pan-acetylated nucleosomes or fragile nucleosomes along gene bodies for Pol II to transcribe. Specifically, for the first round of transcription, the RSC complex works with NuA4 to acetylate histone tails of H2A and H4; the SWI/SNF complex carries SAGA to add acetyl-groups to histone tails of H2B and H3. For the second and subsequent rounds, SWR1 pairs with a piccolo NuA4 to acetylate the histone tails of H2A and H4 of newly inserted nucleosomes, while INO80 pairs with NuA3 to acetylate the histone tails of H2B and H3 within newly inserted nucleosomes along the gene body. After the mission is accomplished, ISW1b couples with Rpd3s to remove acetyl groups on H2A and H4, while CHD1 carries HDA1 along the gene body to remove acetyl groups on H2B and H3.